Bioadsorption of multiple heavy metal ions by Rhizophora Apiculate sp. and Elaesis Guineensis sp. / M.B. Nicodemus Ujih …[et al.] - Nicodemus Ujih, M.B.; Mohamadin, Mohammad Isa; Asli, Millaa-Armila; Mohamed, Bebe Norlita (Universiti Teknologi MARA Shah Alam, 2017)
Heavy metal ions contamination has become more serious which is caused by the releasing of toxic water from industrial area and landfill that are very harmful to all living organism especially human and can even cause death if contaminated in small amount of heavy metal concentration. Currently, peoples are using classic method namely electrochemical treatment, chemical oxidation/reduction, chemical precipitation and reverse osmosis to eliminate the metal ions from toxic water. Unfortunately, these methods are costly and not environmentally friendly as compared to bioadsorption method, where agricultural waste is used as biosorbent to remove heavy metals. Two types of agricultural waste used in this research namely oil palm mesocarp fiber (Elaesis guineensis sp.) (OPMF) and mangrove bark (Rhizophora apiculate sp.) (MB) biomass. Through chemical treatment, the removal efficiency was found to improve. The removal efficiency is examined based on four specification namely dosage, of biosorbent to adsorb four types of metals ion explicitly nickel, lead, copper, and chromium. The research has found that the removal efficiency of MB was lower than OPMF; whereas, the multiple metals ions removal efficiency decreased in the order of Pb2+ > Cu2+ > Ni2+ > Cr2+.